Mahaim Revisited - Eduardo Back Sternick; Damian Sanchez-Quintana; Hein JJ Wellens; Robert H Anderson (Arrhythmia & Electrophysiology Review, 2022)
The name Ivan Mahaim is well-known to electrophysiologists. However, alternative anatomical substrates can produce the abnormal rhythms initially interpreted on the basis of the pathways he first described. These facts have prompted suggestions that Mahaim should be deprived of his eponym. It is agreed that specificity is required when describing the pathways that produce the disordered cardiac conduction, and that the identified pathways should now be described in an attitudinally appropriate fashion. The authors remain to be convinced that understanding will be enhanced simply by discarding the term ‘Mahaim physiology’ from the lexicon. It is fascinating to look back at the history of accessory atrioventricular junctional conduction pathways outside the normal accessory atrioventricular conduction system, and their possible role in rhythm disturbances. It took both the anatomist and the clinical arrhythmologist quite some time to understand the complex anatomical architecture and the ensuing electrophysiological properties. Over the years, the name Mahaim was often mentioned in those discussions, although these pathways were not the ones that produced the eponym. The reason for this review, therefore, is to present relevant information about the person and what followed thereafter.